2013
DOI: 10.1310/hpj4803-213
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacy and Safety of Two Different Insulin Infusion Protocols in the Medical Intensive Care Unit

Abstract: The study showed that by having less intensive glycemic goals, goal BG levels can achieved faster and the rate of severe hypoglycemia can decrease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…The sampling interval remains a critical point for our IIP, like all other IIPs, as it involves a higher workload for nurses and is a nuisance to patients, especially during the night. The median interval between consecutive measurements of 1.8 h in our study is similar to or even longer than that reported by many studies with either paper-based 79,27,29,30 or computer-assisted 38,39 protocols. One-fourth of our BG intervals were longer than 2 h, mostly at night.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The sampling interval remains a critical point for our IIP, like all other IIPs, as it involves a higher workload for nurses and is a nuisance to patients, especially during the night. The median interval between consecutive measurements of 1.8 h in our study is similar to or even longer than that reported by many studies with either paper-based 79,27,29,30 or computer-assisted 38,39 protocols. One-fourth of our BG intervals were longer than 2 h, mostly at night.…”
Section: Discussionsupporting
confidence: 89%
“…The use of DDDiv 140–180 IIP, like the DDDiv 100–139, rapidly achieved the target and maintained it in a large proportion of the measurements, up to 60%, better than with other IIPs with similar BG targets, which range from 36 to 45%. 2730…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations